Determinan Fraudulent Financial Statement Dalam Perspektif Fraud Pentagon Theory - Bisri Rahayuningsih; Sukirman Sukirman (Universitas Katolik Soegijapranata Semarang, 2021)
This study aims to test empirically the determinants of fraudulent financial statement in the perspective of Crowe's fraud pentagon theory in companies that implemented ASEAN Corporate Governance Scorecard in Indonesia. The population of this study are the top rank of 50 companies that implement the ASEAN Corporate Governance Scorecard in 2017-2019. Samples were selected using purposive sampling method. Based on criteria imposed on samples, as much as 63 firm-observations were collected. Test of hypotheses were conducted by using logistic regression analysis. The results show that institutional ownership and financial stability have negative effects on fraudulent financial statement. CEO duality has a positive effect on fraudulent financial statement. However, financial target, external pressure, effective audit committee, quality of external auditor, change in auditor, and change in director have no effects on fraudulent financial statement. Overall, the evident suggests that investors should pay more attention to the quality of financial statements to enhance decision making process.